2014
DOI: 10.1111/1469-0691.12615
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of genetically-determined mannose binding lectin deficiency in young children with invasive pneumococcal disease

Abstract: Susceptibility to invasive pneumococcal disease (IPD) correlates with age, younger children being the group with the highest burden of disease. The relevance of the innate immune response and particularly the role of mannose-binding lectin (MBL) in combating IPD is not well known. This is a 2-year prospective study (February 2011 to March 2013) including patients with IPD who attended two hospitals from Catalonia, Spain. Variables including attack rate of pneumococcal serotype (high or low invasive potential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 36 publications
(70 reference statements)
1
25
0
Order By: Relevance
“…MBL is a circulating protein of the innate immune system and its deficiency has been reported to predispose to IPD [9]. A previous study of our group suggested that a genetically determined low-MBL production could be associated with IPD when disease occurs in children under 2 years of age [24]. In the present study, we also found a significantly higher proportion of MBL2 deficient genotypes among children ≤ 12 months with PM.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…MBL is a circulating protein of the innate immune system and its deficiency has been reported to predispose to IPD [9]. A previous study of our group suggested that a genetically determined low-MBL production could be associated with IPD when disease occurs in children under 2 years of age [24]. In the present study, we also found a significantly higher proportion of MBL2 deficient genotypes among children ≤ 12 months with PM.…”
Section: Discussionsupporting
confidence: 78%
“…In our opinion, this suggests that low invasive capacity serotypes may have more opportunities to cause invasive disease in young children with MBL2 deficient genotypes as their immunity relies specifically in the innate immune system. In our previous study, the frequency of MBL2 deficient genotypes was especially high in younger children with IPD caused by opportunistic serotypes too [24]. At this point, it is important to underline that 13-valent conjugated vaccine would have protected against the main serotypes causing PM in our series, achieving protective antibody titers with prompt vaccination schedules [28].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, serotypes with “high-attack-rate”, also called “high-invasive potential serotypes”, are seldom detected in carriers and often cause IPD particularly in older children and adults without comorbidities [28, 29]. Moreover, we recently reported that young children with genetically-determined low-mannose binding lectine (MBL) production are at a higher risk of developing IPD, particularly that caused by opportunistic or low-attack-rate pneumococcal serotypes [30]. Serotype 1, a well-known high attack serotype, was highly prevalent during the study period mainly associated to pneumonia [17,29], so this could explain a high proportion of disease in healthy children and consequently a low rate of recurrent IPD related with immunological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Also during childhood, the deficiency of MBL biological activity is related to a higher incidence and morbidity for infectious diseases like bronchiolitis [10] or pneumococcal [11] and meningococcal infections [12]. This is particularly true in critical patients, where the deficiency of MBL strongly predisposes to severe sepsis and septic shock [13].…”
Section: Biological and Genetic Aspects Of Mannose Binding Lectinmentioning
confidence: 99%